Performance objectives and performance indicators for Public Private Partnership (PPP) projects in Malaysia - Rosnani binti Mohamad @ Ahmad (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
Public Private Partnership (PPP) has been world widely used as one of the procurement mode by the government. In Malaysia, PPP has been officially introduced in 2006. The present study focuses on two important aspects of PPP implementation that are performance objectives and performance indicators. In particular, there are four objectives of the study that are: 1) to identify the importance performance objectives of PPP in Malaysia; 2) to investigate the differences in the perception between public and private sectors on the importance of performance objectives; 3) to identify the important performance indicators used in assessing PPP performance in terms of the five aspects of PPP which are 'before construction begins', 'financing and markets', 'innovation and learnings', 'stakeholders' perception' and process of lifecycle of PPP project'; and 4) to investigate the differences in the perception between public and private sectors on the importance of performance indicators in terms of the five aspects of PPP. Using a questionnaire survey, 237 completed questionnaires were received representing 51.52% response rate. In examining the importance of performance objective and performance indicators, the descriptive statistical tests of mean, standard deviation and mean score ranking were used. The independent t-tests were conducted to investigate the differences in the perceptions between the two respondents' groups on the importance of performance objectives and performance indicators. The results show that the top three important performance objectives are 'High quality public service', 'Provide convenience service for society' and 'Within or under budget'. In relation to the indicator used in assessing PPP performance, the findings show that the top three important performance indicators before construction begins are 'Project maintainability', 'Commitment and responsibility between public and private sectors' and 'Government's knowledge of PPP' while for financing and markets, the top most important indicators are 'Operational cost', ''Construction cost' and 'Construction period' are perceived as the most important indicators. For innovation and learning, the overall respondents perceived 'Technology innovation', 'Employee training' and 'Financial innovation' as the top three most important indicators whilst 'The satisfaction from public client or government', 'General public/social satisfaction' and 'Good relationship among the concessionaire for the stakeholders' perception component. The top three important indicators for process of lifecycle of PPP project are 'Time management', 'Contractual management' and 'Cost management'. In terms of the differences in the perceptions between the public and private sector groups, the test results indicate that there are only significant statistical differences for one performance objective and few performance indicators for three out of five performance indicators components. The findings of the present study contribute to both knowledge and practice especially to the policy makers in ensuring better implementation of PPP in future.